Layered double hydroxide crystals and anion adsorbents

By producing layered double hydroxide crystals through high-temperature synthesis and subsequent treatments, the aggregation issue is resolved, achieving superior ion exchange capacity and effective removal of harmful anions like nitrate and arsenic.

JP7609473B2Active Publication Date: 2025-01-07SHINSHU UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023073641
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-08-24
Filing Date
2023-04-27
Publication Date
2025-01-07
Estimated Expiration
2039-08-23

AI Technical Summary

Technical Problem

Conventional methods for synthesizing layered double hydroxide crystals result in nanometer-sized particles that aggregate easily, leading to reduced ion exchange capacity, which is insufficient for effectively removing harmful anions like nitrate ions and arsenic from water.

Method used

A method involving the production of precursor crystals by heating a raw material mixture with an excess of a Na source substance at high temperatures, followed by hydrolysis and reduction treatments, maintains a tabular laminated structure, resulting in layered double hydroxide crystals with uniform grain sizes and improved dispersibility.

Benefits of technology

The resulting crystals exhibit higher ion exchange capacity, effectively removing harmful anions such as nitrate ions and arsenic from water, with enhanced dispersibility preventing aggregation and maintaining high performance in various environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609473000001
    Figure 0007609473000001
  • Figure 0007609473000002
    Figure 0007609473000002
  • Figure 0007609473000003
    Figure 0007609473000003
Patent Text Reader

Abstract

To provide layered double hydroxide crystals that realize higher ion exchange capacity than conventional ones.SOLUTION: Layered double hydroxide crystals are provided in which a plurality of plate-like crystals is composed of a structure which is represented by a formula (1) below and in which host and guest layers are alternately stacked. The layered double hydroxide crystals are composed of a plurality of crystal grains having a stacked structure in which the plate-like crystals are stacked. The grain sizes in the width direction of the plurality of crystal grains are all in a range of 0.1 μm to 20.0 μm. [Ni2+1-xCo3+x(OH)2] [(CO32-)X / 2] (1) (where 0.2<x≤0.33).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a layered double hydroxide crystal and an anion adsorbent, and in particular to a layered double hydroxide crystal for removing harmful anions from water or soil. This application claims priority based on Japanese Patent Application No. 2018-157573, filed on August 24, 2018, the contents of which are incorporated herein by reference. [Background technology]

[0002] Layered double hydroxides (LDHs) are inorganic anion exchangers, and are layered inorganic compounds consisting of alternating layers of metal oxides (host layers) and anionic species or water molecules (guest layers). Since the anionic species in the guest layers can be exchanged with anionic species in solution while maintaining the layered structure, they are known to exhibit highly selective ion exchange properties by utilizing the interlayer (two-dimensional space).

[0003] Conventionally, the selective ion exchange properties of LDHs have been much discussed. For example, an adsorbent having Mg-Al hydrotalcite has been devised as an adsorbent capable of simultaneously and selectively adsorbing nitrate ions, phosphorus, and arsenic from an aqueous solution (see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-178682 A Summary of the Invention [Problem to be solved by the invention]

[0005] Currently, more than 1.1 billion people in the world have difficulty obtaining safe drinking water. In addition, large-scale natural disasters have been increasing in recent years, so securing safe water in emergencies when disasters occur is an urgent need, but a concrete solution has not yet been found. The background to these social problems is the fact that soil pollution is progressing in various countries and regions due to industrial wastewater, or agricultural fertilizers are mixed into groundwater due to the application of the fertilizers. In particular, harmful anion species such as nitrate ions generated from industrial wastewater and agricultural fertilizers accumulate in the human body and have a significant impact, so there is a demand for layered double hydroxides that can fully remove harmful anion species.

[0006] However, in the precipitation method, which is a common method for synthesizing LDHs crystals, the synthesis temperature is relatively low, from room temperature to about 80°C, and the crystals do not grow sufficiently, resulting in the formation of many nm-sized crystal particles. Therefore, the crystal particles tend to aggregate in water or in a humid atmosphere, which results in a decrease in the ion exchange capacity of the LDHs, and a problem occurs in which sufficient ion exchange ability cannot be obtained.

[0007] An object of the present invention is to provide a layered double hydroxide crystal and an anion adsorbent which realize a higher ion exchange capacity than conventional ones. [Means for solving the problem]

[0008] As a result of intensive research, the present inventors have found that when producing a layered double hydroxide, a precursor crystal having a plate-like layered structure different from conventional ones can be formed by heating a raw material containing a Na source substance, which serves as a Na source, in an amount greater than the stoichiometric ratio of the precursor crystal at a high temperature. They also found that when the obtained precursor crystal is subjected to hydrolysis treatment and reduction treatment, the plate-like layered structure of the precursor crystal is maintained, and as a result, layered double hydroxide crystals having a plate-like layered structure can be obtained with high dispersibility.

[0009] That is, the gist and configuration of the present invention are as follows. [Claim 1] The plate-like crystals are represented by the following formula (1) and are a layered double hydroxide having a structure in which host layers and guest layers are alternately laminated, The plate-like crystals are stacked on each other to form a multi-layer structure. The grain size in the width direction of the plurality of crystal grains is uniform within a range of 0.1 μm to 20.0 μm. 2+ 1-x Co 3+ x (OH)2]·[(CO3 2- ) X / 2 ] …(1) (Here, 0.2 <x≦0.33) [Claim 2] The plate-like crystals are represented by the following formula (2), and are layered double hydroxides having a structure in which host layers and guest layers are alternately laminated, The plate-like crystals are stacked on each other to form a multi-layer structure. The grain size in the width direction of the plurality of crystal grains is uniform within a range of 0.1 μm to 20.0 μm. 2+ 1-x Co 3+ x (OH)2]·[(Cl - ) X ] …(2) (Here, 0.2 <x≦0.33) [Claim 3] A layered space is formed between adjacent plate-like crystals, The layered double hydroxide crystal according to the above [1] or [2], wherein the plurality of plate-like crystals and the plurality of layered spaces are arranged alternately. [Claim 4] An anion adsorbent comprising the layered double hydroxide crystal according to any one of the above [1] to [3]. [Claim 5] The anion adsorbent according to the above [4], which adsorbs one or more anions selected from nitrate ions and arsenide ions. Effect of the Invention

[0010] According to the present invention, it is possible to provide layered double hydroxide crystals having a higher ion exchange capacity than conventional ones. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1(a) is a schematic diagram showing the structure of a layered double hydroxide crystal according to an embodiment of the present invention, and FIG. 1(b) is an electron microscope image showing the structure of one crystal grain that constitutes the layered double hydroxide crystal. [Diagram 2] 2(a) to (d) are schematic diagrams illustrating the method for producing layered double hydroxide crystals according to this embodiment. [Diagram 3] 1 is a graph showing the results of measuring the diffraction intensity by powder X-ray diffraction (XRD) for the precursor crystals, the crystals after oxidative hydrolysis treatment, and the crystals after reduction treatment obtained in the examples. [Figure 4] FIG. 4(a) is an FE-SEM image of the layered double hydroxide crystal obtained in the example, and FIG. 4(b) is an enlarged image thereof. [Diagram 5] FIG. 5(a) is an FE-SEM image of the layered double hydroxide crystals obtained by the solid phase method as Comparative Example 1, and FIG. 5(b) is an enlarged image thereof. [Figure 6] FIG. 6(a) is an electron microscope image of the double hydroxide crystals obtained by the homogeneous precipitation method as Comparative Example 2, and FIG. 6(b) is an enlarged image thereof. [Figure 7] FIG. 7 is a graph showing the results of measuring the ion exchange capacity (Kd) for nitrate ions for the double hydroxide crystals obtained in Example and Comparative Examples 1 and 2. [Figure 8] FIG. 8 is a graph showing the relationship between the equilibrium concentration (Ce) and the amount of nitrate ion adsorption (qe) for the double hydroxide crystals obtained in Example and Comparative Examples 1 and 2. [Figure 9] FIG. 9(a) shows the results of cross-sectional line analysis performed in the in-plane direction of the plate crystals in the layered double hydroxide crystals obtained in Example 1, and FIG. 9(b) shows the results of cross-sectional line analysis performed in the in-plane direction of the plate crystals in Comparative Example 1. [Figure 10]FIG. 10(a) shows the results of cross-sectional line analysis performed in the stacking direction of the plate crystals in the layered double hydroxide crystals obtained in Example 1, and FIG. 10(b) shows the results of cross-sectional line analysis performed in the stacking direction of the plate crystals in Comparative Example 1. [Figure 11] FIG. 11 is a graph showing the results of determining the removal rates of fluoride ions and arsenide ions for the layered double hydroxide crystals obtained in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.

[0013] [Structure of layered double hydroxide crystals] FIG. 1(a) is a schematic diagram showing the structure of a layered double hydroxide crystal according to this embodiment, and FIG. 1(b) is an electron microscope image showing the structure of one crystal grain that constitutes the layered double hydroxide crystal.

[0014] The layered double hydroxide crystal 1 (hereinafter also referred to as LDHs crystal) is represented by the following formula (1), and as shown in Figures 1(a) and 1(b), is composed of a plurality of crystal grains 10 having a layered structure in which a plurality of plate-like crystals 11, 11, ... are stacked, and the grain sizes of the plurality of crystal grains 10, 10, ... are uniform on the microscale. [Ni 2+ 1-x Co 3+ x (OH)2]·[(CO3 2- ) X / 2 ] …(1) (Here, 0.2 <x≦0.33) The layered double hydroxide crystal 1 may be anhydrous or may be a hydrate containing a small amount of water (H2O).

[0015] A layered space 12 is formed between adjacent plate crystals 11, 11, and a plurality of plate crystals 11, 11, . . . and a plurality of layered spaces 12, 12, .

[0016] When the crystal grain 10 is observed under magnification, the plate crystal 11 can also be called a thin plate crystal or a sheet crystal. The plate crystal 11 has a thickness on the order of submicrons, and the layered spaces 12 also have intervals on the order of submicrons (FIG. 1(b)). The crystal grain 10 is constituted by a layered structure in which a plurality of these plate crystals 11, 11, ... are layered in several to several tens of layers. The grain size or circle equivalent diameter in the width direction of the plate crystal 11 is 0.1 μm to 20.0 μm, and preferably 1.0 μm to 5.0 μm.

[0017] The crystal grains 10 are anion-exchangeable inorganic ion exchangers, and can also be called layered inorganic compounds consisting of a structure in which host layers (metal hydroxides) and guest layers (anion species and water molecules) are alternately laminated. The anion species in the guest layers can be exchanged with anion species in a solution while maintaining the layered structure, and therefore exhibit highly selective ion exchange properties by utilizing the interlayer (also called two-dimensional space).

[0018] In the above formula (1), Ni 2+ is not limited to being fully substituted, but may be partially substituted. 3+ Similarly, it is not limited to full substitution, and may be partial substitution.

[0019] The LDHs crystal of the present embodiment may be a crystal represented by the following formula (2), which is composed of a plurality of crystal grains having a layered structure in which a plurality of plate-like crystals are layered, and the grain sizes of the plurality of crystal grains may be uniform on a microscale. The LDHs crystal may be a crystal represented by the above formula (1) that is composed of carbonate ions (CO 2- ) is chloride ion (Cl - ) is replaced with the crystal represented by formula (1) above. [Ni 2+ 1-x Co 3+ x (OH)2]·[(Cl - ) X ] …(2) (Here, 0.2 <x≦0.33)

[0020] [Method of manufacturing layered double hydroxide crystals] Next, a method for producing the layered double hydroxide crystals 1 will be described. 2(a) to (d) are schematic diagrams illustrating the method for producing layered double hydroxide crystals according to this embodiment.

[0021] First, a raw material is prepared by further adding a Na source material to a mixture of a Ni source material, a Co source material and a Na source material which are mixed based on the stoichiometric ratio of the precursor crystal described below. Examples of Ni sources include NiO, Ni(OH)2, Ni(NO3)2, Ni(NO3)2·6H2O, NiCO3, NiSO4, NiSO4·6H2O, NiCl2NiCl2·6H2O, (HCOO)2Ni, (HCOO)2Ni·2H2O, C2O4Ni, C2O4Ni·2H2O, (CH3COO)2Ni, (CH3COO)2Ni·4H2O, Ni(CH3COCHCOCH3), Ni(CH3COCHCOCH3)·xH2O, NiCO3, NiCO3·xH2O, (NH4)2Ni(SO4)2, (NH4)2Ni(SO4)2·6H2O, and Ni.

[0022] Examples of Co sources include Co3O4, Co(OH)2, CoCl2, CoCl2·6H2O, Co(NO3)2, Co(NO3)2·6H2O, CoSO4, CoSO4·7H2O, x2CoCO3·Co(OH)2, CoCO3, CoCO3·xH2O, C2O4Co, C2O4Co·2H2O, C2O4Co, Co(NH4)2(SO4)2, Co(NH4)2(SO4)2·6H2O, Co(CH3COCHCOCH3), Co(SCN)2, Co(SCN)2 / xH2O, (CH3COO)2Co, (CH3COO)2Co·4H2O, C 10 H 14 CoO4, C 10 H 14 Examples include CoO4·xH2O, [Co(NH3)6]Cl3, and Co.

[0023] Examples of the Na source material include NaNO3, Na2CO3, Na2SO4, Na2SO4·10H2O, Na2SO3, NaCl, CH3COONa, CH3COONa, CH3COONa·3H2O, C2O4Na2, C6H5Na3O7, C6H5Na3O7·2H2O, and NaHCO3. The content of the Na source material in the above raw materials is preferably in excess of the content based on the stoichiometric ratio of the precursor crystal, more preferably 1.1 times or more and 10 times or less, and even more preferably 1.5 times or more and 5.0 times or less with respect to the stoichiometric ratio.

[0024] Next, the above raw materials are heated at 600 to 1000 °C for 1 hour or more to produce a precursor crystal composed of NaNi 1-x Co x O2 crystal (0.2 < x ≤ 0.33) (Figure 2(a)). The method of crystal growth using a high-temperature molten salt in this way can also be called the flux method. In this embodiment, the precursor crystal is produced by the flux method.

[0025] In the flux method of this embodiment, N a A raw material in which the source material is added in an amount more than the stoichiometric ratio, preferably N a A precursor crystal is produced by heating a raw material in which the source material is added in excess of the above stoichiometric ratio at a high temperature. Thereby, highly crystalline particles with well-developed self-form can be grown on the micro-order, and a precursor crystal having a laminated structure in which a plurality of plate-like crystals are laminated can be obtained.

[0026] In this heat treatment step, specifically, the above raw materials can be heated, held, and cooled to produce the above precursor crystal. The heating rate condition and the cooling condition in this heat treatment step are not particularly limited. For example, the heating rate is 45 °C / h to 1600 °C / h, the holding temperature is 700 to 1000 °C, the holding time is 0.1 to 20 hours, the cooling rate is 0.1 to 60000 °C / h, the stopping temperature is 500 °C or lower, and the air-cooling temperature is, for example, room temperature.

[0027] After that, NaNi 1-x Co xA precursor crystal composed of O2 crystals is hydrolyzed (Figure 2(b)). The method of hydrolysis is not particularly limited, but for example, the precursor crystal can be subjected to oxidative hydrolysis using an alkali. This hydrolysis process expands the spacing between adjacent plate crystals while maintaining the shape of the multiple plate crystals in the precursor crystal.

[0028] Next, the crystals obtained by hydrolysis of the precursor crystals are reduced (FIG. 2(c)). There are no particular limitations on the method of reduction, but for example, reduction can be performed using a salt of a strong acid and a strong alkali. This reduction process retains carbonate ions between the metal hydroxide layers while maintaining the shape and position of the multiple plate-like crystals after the hydrolysis, thereby obtaining crystal grains having the layered double hydroxide crystals represented by the above formula (1).

[0029] After the reduction treatment, the carbonate ions located between the layers of the crystals obtained by the reduction treatment may be replaced with chloride ions (FIG. 2(d)). There are no particular limitations on the method of this replacement treatment, but for example, an acid such as hydrochloric acid can be used for replacement. This replacement treatment step retains the chloride ions between the metal hydroxide layers while maintaining the shape and position of the multiple plate-like crystals after the reduction treatment, thereby obtaining crystal grains having the layered double hydroxide crystals represented by the above formula (2).

[0030] As described above, according to this embodiment, the layered double hydroxide crystal 1 is composed of a plurality of crystal grains 10 represented by the above formula (1) or formula (2) and having a laminated structure in which a plurality of plate-like crystals 11 are laminated, and the particle sizes of the plurality of crystal grains 10, 10, ... are uniform on the microscale, so that the layered double hydroxide crystal 1 has higher dispersibility than conventional crystal grains, and can thereby realize high ion exchange capacity. Therefore, the crystal grains 10 are unlikely to aggregate with each other, for example, even in water or a humid atmosphere, and as a result, the ion exchange capacity of the layered double hydroxide crystal 1 is increased, and sufficient ion exchange capacity can be obtained. In particular, harmful anion species such as nitrate ions generated from industrial wastewater and agricultural fertilizers can be easily and sufficiently removed.

[0031] Also, according to this embodiment, a raw material adjusted by adding a further Na source material to a mixture of a Ni source material, a Co source material, and a Na source material mixed based on the stoichiometric ratio of the precursor crystal is heated at 600°C to 1000°C for 1 hour or more to obtain NaNi 1-x Co x O2 crystals (0.2 < x ≤ 0.33) to grow precursor crystals having a higher dispersibility than before on a microscale. As a result, a layered double hydroxide crystal 1 having a higher ion exchange capacity than before can be produced.

Examples

[0032] Hereinafter, examples of the present invention will be described. The present invention is not limited only to the following examples.

[0033] First, NaNi 0.7 Co 0.3 O2 crystals were produced by the flux method. As starting materials, NiO, Co3O4, and NaNO3 were used as solutes. The case where NaNO3 was added in excess of the stoichiometric ratio of the target crystal (precursor crystal) and formulated as a self-flux was used as the flux method (FLUX) and used as the raw material for Example 1. At this time, the solutes (NiO, Co3O4, and NaNO3) composed of the stoichiometric ratio and NaNO3 as the flux were adjusted to be 100:40 in Mol%. Also, for comparison, the case where the same procedure as in the above example was carried out except that NaNO3 was formulated according to the stoichiometric ratio of the target crystal was used as the solid-phase method (SSR) and used as the raw material for Comparative Example 1.

[0034] Each of the raw materials prepared as described above was dry-mixed and filled into an alumina crucible, and then heated in a muffle furnace at a heating rate of 500°C / h, a holding temperature of 800°C, and a holding time of 10 hours. Then, the cooling rate was 200°C / h and the stop temperature was 500°C, and it was allowed to cool to room temperature to obtain NaNi 0.7 Co 0.3O2 crystals were obtained. The obtained powder was subjected to oxidative hydrolysis treatment using a solution of NaClO2.1Mol / L and KOH2.0Mol / L at a solid-liquid ratio of 0.1L / g and a stirring time of 24 hours. The obtained crystals were then subjected to reduction treatment three times using a solution of H2O20.02Mol / L, NaCl0.021Mol / L, a solid-liquid ratio of 0.1L / g, and a stirring time of 24 hours to obtain the LDHs crystals of Example 1 and Comparative Example 1 represented by the above formula (1).

[0035] Further, after carrying out a reduction treatment to obtain the LDHs crystals of Example 1, a substitution treatment was carried out using a solution of 1.0 mol of NaCl and 3.2 mMol of HCl at a solid-liquid ratio of 0.1 L / g for a reaction time of 24 hours to obtain the LDHs crystals of Example 2 represented by the above formula (2).

[0036] As another comparison, crystals were also prepared by the homogeneous precipitation method (COP). l 2·6H2O, CoCl2·6H2O, hexamethylenetetramine (HMT) and polyvinylpyrrolidone (PVP) were dissolved in ultrapure water, and the mixed solution was stirred at 90°C for 1 hour to obtain the double hydroxide crystals of Comparative Example 2.

[0037] The double hydroxide crystals of Example 1 and Comparative Examples 1 and 2 were measured and evaluated by the following methods. (Structure of double hydroxide crystals) For Example 1, the crystal structures of the precursor crystals, the crystals after oxidative hydrolysis treatment, and the crystals after reduction treatment (LDHs crystals) were identified using a powder X-ray diffraction (XRD) apparatus (Rigaku Corporation, "MiniFlexII") respectively. Furthermore, the crystal morphology and cross-sectional structure of Example 1 and Comparative Examples 1 and 2 were observed with a field emission scanning electron microscope (FE-SEM) (manufactured by JEOL, "JSM-7400F"). Furthermore, the composition distribution in the cross section of Example 1 and Comparative Example 1 was analyzed using a scanning electron microscope (manufactured by JEOL, "JSM-7000F") by energy dispersive X-ray spectroscopy (EDS).

[0038] (Evaluation of ion exchange capacity (1)) The anion exchange performance of the double hydroxide crystals of Example 1 and Comparative Examples 1 and 2 was evaluated under the following conditions. First, as a pretreatment, each crystal powder was immersed in a mixed aqueous solution of 3.0 mMol of HCl and 4.0 Mol of NaCl to replace the anion species of the guest layer with chloride ions. Then, the crystal powder was immersed in a 0.1 to 100 mMol / L NaNO3 aqueous solution and stirred at 25°C for 24 hours using a cool stirrer. At this time, the solid-liquid ratio was fixed at 1.0 g / L. After immersion, the powder was separated from the aqueous solution, and the nitrate ion concentration of the supernatant was quantified using a suppressor-type ion chromatograph (Shimadzu Corporation, "HIC-SP").

[0039] First, the crystals obtained in each step of Example 1 were measured for diffraction intensity by powder X-ray diffraction (XRD), and the results are shown in FIG. In Example 1, it was confirmed from the diffraction lines in the profile diagram that by subjecting the precursor crystals grown by the flux method to oxidative hydrolysis treatment and three reduction treatments, LDHs crystals in which the layered structure of the precursor crystals was largely maintained were obtained.

[0040] Next, FE-SEM images of the crystals obtained in Example 1 and Comparative Examples 1 and 2 are shown in FIGS. In the LDHs crystals of Example 1 obtained by the flux method, crystal grains having a grain size of several μm were present with a relatively uniform grain size and high dispersibility (FIG. 4(a)). Each crystal grain had a layered structure in which multiple plate-like crystals were layered (FIG. 4(b)).

[0041] On the other hand, in the LDHs crystals of Comparative Example 1 obtained by the solid phase method, there were multiple crystal grains with a grain size of several tens of μm, and the grain size varied in the range of 5 μm to 50 μm. Therefore, it was found that the grain size varied more and the dispersibility was lower than in Example 1 (FIGS. 5(a) and 5(b)).

[0042] Furthermore, in the double hydroxide crystals of Comparative Example 2 obtained by the homogeneous precipitation method, plate-like crystals having a particle size of 100 nm formed aggregates in random directions, and it was found that a layered structure of the plate-like crystals was not formed (Figures 6(a) and 6(b)).

[0043] Next, the results of the evaluation (1) of the ion exchange capacity for Example 1 and Comparative Examples 1 and 2 are shown in FIG. 7. In the evaluation (1) of the ion exchange capacity, nitrate ions were used as the anions to be removed. The vertical axis of the graph is K d indicates K d =q e / C e (q e : Adsorption amount of nitrate ions (mg / g), C e : Nitrate ion equilibrium concentration (mg / mL). NO3 - The initial concentration was 1.0 mMol. As shown in FIG. 7, the K of Example 1 obtained by the flux method d is the K of Comparative Example 1 obtained by the solid phase method d Compared with the homogeneous precipitation method, the K d This is about 5 times higher than that of Example 1, which is the highest value. In particular, when a very small amount of ion is exchanged, there is no interaction between ions, and the selectivity specific to the ion exchange site is reflected. This shows that the LDHs crystals of Example 1 have high nitrate ion exchange ability.

[0044] Next, the results of examining the adsorption isotherms of the crystals obtained in Example 1 and Comparative Examples 1 and 2 are shown in FIG. 8. The adsorption isotherms of Example 1 and Comparative Examples 1 and 2 are e The amount of nitrate ions adsorbed in e was plotted and calculated by the least squares method. The Langmuir equation, which is used for comparison, is a theoretical adsorption isotherm that assumes that all ion adsorption sites are equivalent and that one ion exchange site binds only one adsorbent. In addition, the dependent variable (q e ) as the independent variable (C e ) represents the index that can be determined by 2 The value was calculated.

[0045] As a result, in Example 1 obtained by the flux method, R 2 value is 0.98, and the saturated adsorption amount q s In Comparative Example 1, R2 value is 0.90, and the saturated adsorption amount q s In Comparative Example 2, R 2 value is 0.75, and the saturated adsorption amount q s That is, the R in Example 1 was 15.7 mg / g. 2 It was found that the adsorption isotherm of Example 1 was most compatible with the Langmuir equation. From this, it can be inferred that the LDHs crystals of Example 1 had crystal grains with uniform ion exchange sites (also called ion adsorption sites).

[0046] Next, in order to consider the improvement of the ion exchange capacity, the BET specific surface area (m 2 The BET specific surface area was calculated based on the BET equation by measuring the nitrogen gas adsorption isotherm of each crystal using a gas adsorption apparatus (Microtrack-Bel, "BELSORP Mini II").

[0047] As a result, in Example 1, the BET specific surface area was 12.37 m 2 / g, whereas in Comparative Example 1, it was 12.86 m 2 / g, and 4.13 m in Comparative Example 2. 2 / g. That is, the BET specific surface area of ​​Example 1 was about three times that of Comparative Example 2. From this, it can be inferred that the ion exchange capacity of the LDHs crystals of Example 1 was improved with an increase in the specific surface area.

[0048] Furthermore, the LDHs crystals obtained in Example 1 and Comparative Example 1 were subjected to cross-sectional line analysis. The O, Ni, Co, and Cl elements were measured in the in-plane direction of the plate crystal in a cross section in the stacking direction of one crystal grain constituting the LDHs crystal obtained in Example 1. Similarly, the above elements were measured in the in-plane direction of the plate crystal in a cross section in the stacking direction of one crystal grain constituting the LDHs crystal obtained in Comparative Example 1.

[0049] As a result, it was found that in Example 1 obtained by the flux method, Ni elements were distributed uniformly in the in-plane direction of the plate crystals, and Co elements were also distributed uniformly (FIG. 9(a)).

[0050] On the other hand, in Comparative Example 1 obtained by the solid phase method, it was found that there was variation in the distribution of Ni elements and also in the distribution of Co elements with respect to the in-plane direction of the plate crystals (FIG. 9(b)).

[0051] Furthermore, the O, Ni, Co and Cl elements were measured in the stacking direction of the plate crystals in a cross section in the stacking direction of one crystal grain constituting the LDHs crystal obtained in Example 1. Similarly, the above elements were measured in the stacking direction of the plate crystals in a cross section in the stacking direction of one crystal grain constituting the LDHs crystal obtained in Comparative Example 1.

[0052] As a result, it was found that in Example 1 obtained by the flux method, Ni elements were distributed uniformly in the lamination direction of the plate crystals, and Co elements were also distributed uniformly (FIG. 10(a)).

[0053] On the other hand, in Comparative Example 1 obtained by the solid phase method, it was found that there was variation in the distribution of Ni elements and also in the distribution of Co elements in the stacking direction of the plate crystals (FIG. 10(b)).

[0054] From these results, it is inferred that by generating precursor crystals by high-temperature heating using the flux method, uniform diffusion paths are created within the crystal grains that make up the LDHs crystals, making it possible to effectively utilize more ion exchange sites, thereby improving the ion exchange capacity.

[0055] (Evaluation of ion exchange capacity (2)) Next, for Example 2, evaluation (2) of the ion exchange capacity was carried out using fluoride ions and arsenide ions as the anions to be removed.

[0056] In the fluorine test, the crystal powder of Example 2 was immersed in an aqueous NaF solution and stirred at 25°C for 24 hours using an autoshaker (RT, 150 rpm). At this time, the initial concentration of fluoride ions was 1.33 mMol / L, and the solid-liquid ratio was fixed at 1.0 g / L. After immersion, the powder was separated from the aqueous solution, and the fluoride ion concentration of the supernatant was quantified using the suppressor-type ion chromatograph, and the removal rate of fluoride ions was calculated from the initial concentration value. The results are shown in Figure 11.

[0057] For arsenic testing, the test solution was prepared according to the guidelines for NSF53 arsenic-removed water as specified in the NSF / ANSI53 "Drinking Water Treatment Units - Health Effects" standard document. The crystal powder of Example 2 was placed in a designated container and slurried with an arsenic test solution with an initial concentration of 0.050 mg / L. The resulting slurry was agitated by rotating the container for several hours. After agitation, the test solution was separated from the powder by filtration through a filter. The arsenide ion concentration in the filtrate was quantified using the suppressor-type ion chromatograph described above, and the arsenide ion removal rate was calculated from the initial concentration value. The results are shown in Figure 11.

[0058] As shown in FIG. 11, when the LDHs crystal of Example 2 was used, the fluoride ion concentration in the supernatant was 0.33 Mol / L, and the removal rate of fluoride ions was 75%. In addition, no arsenide ions were detected in the filtrate, and the removal rate of arsenide ions was about 100%. From this, it was found that the LDHs crystal of Example 2 has high fluoride ion exchange capacity and high arsenide ion exchange capacity in addition to high nitrate ion exchange capacity, and exhibits high removal properties for harmful anion species. It was also found that it exhibits extremely high removal properties, especially for nitrate ions and arsenide ions. [Industrial Applicability]

[0059] The layered double hydroxide crystal of the present invention can be used as an anion-adsorbing material that adsorbs anions, and thus can be applied to anion adsorbents used in various industrial fields. [Explanation of symbols]

[0060] 1. Layered double hydroxide crystals 10 Grains 11 Plate-like crystals 12 Layered Space

Claims

1. The plate-like crystals are a layered double hydroxide represented by the following formula (1) and have a structure in which host layers and guest layers are alternately laminated, The plate-like crystals are stacked on each other to form a multi-layer structure. The grain sizes of the plurality of crystal grains in the width direction are uniform within a range of 0.1 μm to 20.0 μm, A layered space is formed between adjacent plate-like crystals, The layered double hydroxide crystals are formed by alternating the plate-like crystals and the layered spaces. [Ni 2+ 1-x Co 3+ x (OH) 2 ]・[(CO 3 2- ) X/2 ] …(1) (where 0.2<x≦0.33)

2. The plurality of plate-like crystals are represented by the following formula (2), and are a layered double hydroxide having a structure in which host layers and guest layers are alternately laminated, The plate-like crystals are stacked on each other to form a multi-layer structure. The grain sizes of the plurality of crystal grains in the width direction are uniform within a range of 0.1 μm to 20.0 μm, A layered space is formed between adjacent plate-like crystals, The layered double hydroxide crystals are formed by alternating the plate-like crystals and the layered spaces. [Ni 2+ 1-x Co 3+ x (OH) 2 ]・[(C- - ) X ] …(2) (where 0.2<x≦0.33)

3. An anion adsorbent comprising the layered double hydroxide crystal according to claim 1 or 2.

4. The anion adsorbent according to claim 3, which adsorbs one or more anions selected from nitrate ions and arsenide ions.

Citation Information

Patent Citations

  • Selective adsorbent and its production method

    JP2009178682A

  • Layered double hydroxide having i3-, and method for producing the same

    JP2012240873A